The HEARTS app: a clinical tool for cardiovascular risk and hypertension management in primary health care - Pedro Ordunez; Carlos Tajer; Thomas Gaziano; Yenny A. Rodriguez; Andres Rosende; Marc G. Jaffe (Pan American Health Organization, 2022)
HEARTS in the Americas is the regional adaptation of the World Health Organizations Global Hearts Initiative, which will be the model for risk management for cardiovascular disease (CVD) in primary health care in the Region of the Americas by 2025. It has already been implemented in 21 countries and 1045 primary health care centers throughout Latin America and the Caribbean. It takes a public health and health systems approach to systematically introduce simplified interventions at the primary health care level and focuses on hypertension as a clinical entry point. This paper introduces a new, improved application (app), the main component of which is the calculator for CVD risk and hypertension management. The paper summarizes the risk assessment approach and the methodology used by the World Health Organization to update its cardiovascular risk charts in 2019; describes the app, its use, functionality and validation process; and provides a set of practical recommendations for optimizing CVD risk and hypertension management by using the app in clinical practice. The HEARTS app is a powerful tool to improve the quality of care provided in primary health settings. The creation and dissemination of the HEARTS app is an essential step in the journey towards eliminating preventable CVD in the Americas.